2019
DOI: 10.1016/j.waojou.2019.100021
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial dysbiosis is associated with allergen-specific IgE responses in young children with airway allergies

Abstract: Background There is increasing evidence linking alterations of the gut microbial composition during early infancy to the development of atopic diseases and asthma. However, few studies have addressed the association of dysbiotic gut microbiota with allergic reactions through evaluation of feces in young children with allergic airway diseases. Methods We sought to evaluate relationships among gut microbiota, total fecal immunoglobulin E (IgE) levels, serum allergic sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 41 publications
4
89
2
1
Order By: Relevance
“…Both the ACE and Shannon indices reflected a reduction in the bacterial diversity and richness in CSU patients, which is highly consistent with other allergic diseases (Bisgaard et al, 2011). At the phylum level, when compared with healthy controls, there was a relative reduced abundance of Bacteroidetes and Firmicutes in CSU patients, which is partly in agreement with the airway allergies in young children (Chiu et al, 2019). At the genus level, members of the Bacteroides, Faecalibacterium, Bifidobacterium, Lactobacillus, and unidentified Ruminococcaceae were relatively lower and members of unidentified Enterobacteriaceae were relatively increased compared to healthy controls, which is partly consistent with previous studies about CU or allergic diseases (Sjogren et al, 2009;Johansson et al, 2011;Candela et al, 2012;Nabizadeh et al, 2017;Rezazadeh et al, 2018;Chiu et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Both the ACE and Shannon indices reflected a reduction in the bacterial diversity and richness in CSU patients, which is highly consistent with other allergic diseases (Bisgaard et al, 2011). At the phylum level, when compared with healthy controls, there was a relative reduced abundance of Bacteroidetes and Firmicutes in CSU patients, which is partly in agreement with the airway allergies in young children (Chiu et al, 2019). At the genus level, members of the Bacteroides, Faecalibacterium, Bifidobacterium, Lactobacillus, and unidentified Ruminococcaceae were relatively lower and members of unidentified Enterobacteriaceae were relatively increased compared to healthy controls, which is partly consistent with previous studies about CU or allergic diseases (Sjogren et al, 2009;Johansson et al, 2011;Candela et al, 2012;Nabizadeh et al, 2017;Rezazadeh et al, 2018;Chiu et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…At the phylum level, when compared with healthy controls, there was a relative reduced abundance of Bacteroidetes and Firmicutes in CSU patients, which is partly in agreement with the airway allergies in young children (Chiu et al, 2019). At the genus level, members of the Bacteroides, Faecalibacterium, Bifidobacterium, Lactobacillus, and unidentified Ruminococcaceae were relatively lower and members of unidentified Enterobacteriaceae were relatively increased compared to healthy controls, which is partly consistent with previous studies about CU or allergic diseases (Sjogren et al, 2009;Johansson et al, 2011;Candela et al, 2012;Nabizadeh et al, 2017;Rezazadeh et al, 2018;Chiu et al, 2019). For example, Nabizadeh et al (2017) and Rezazadeh et al (2018) reported a depletion in the relative amounts of Faecalibacterium prausnitzii, Clostridia, Akkermansia muciniphila, Bifidobacterium, and Lactobacillus in CU patients.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It was hypothesized that commensal‐driven signals limit isotype switching to IgE and direct it towards IgA and reduce levels of circulating basophils which in turn alleviates lung inflammation . A recent study revealed that antigens contributing to childhood airway diseases were associated with alterations in the composition of gut microbiota and elevated levels of faecal IgE . Another study showed that early exposure to intestinal microbiota reduces the levels of invariant natural killer T (iNKT) cells which produce IL‐4 and IL‐13 that accumulate in the lungs of GF mice and promote isotype switching to IgE .…”
Section: The Link Between the Pathogenesis Of Asthma And Dysbiosismentioning
confidence: 99%
“…4,29 A recent study revealed that antigens contributing to childhood airway diseases were associated with alterations in the composition of gut microbiota and elevated levels of faecal IgE. 33 Another study showed that early exposure to intestinal microbiota reduces the levels of invariant natural killer T (iNKT) cells which produce IL-4 and IL-13 that accumulate in the lungs of GF mice and promote isotype switching to IgE. 34 An increase in iNKT cells caused by microbial deficiency leads to increased susceptibility to asthma (Figures 1 and 2).…”
Section: Pathogenesis Of Asthma and Dysbiosismentioning
confidence: 99%